INTEGRATED EDUCATION AS A SOLUTION FOR EDUCATIONAL DUALISM FROM SAID NURSI’S PERSPECTIVE - Embong, Rahimah; Rahman, Amilah Awang Abdul; Ibrahim, Mohamed; Abdullah, Ridhuan Tee; Adam, Fadzli; Omar, Syed Hadzrullathfi Syed; Wahid, Najihah Abdul; Omar, Nor Afizan Che (PEOPLE: International Journal of Social Sciences, 2017)
This paper aims to analyze the concept of integrated curriculum according to Badiuzzaman Said Nursi (1877-1960) based on his educational model that is Madrasah al-Zahra. This attempts to help in deriving some possible answers as solution of educational dualism facing the Muslim society today. It is a fact that the Ummatic malaise is rooted from educational dualism, co-existence of traditional religious and modern secular systems of education as a negative impact of Western colonialization and secularization. The integration of both traditional religious and modern secular sciences into an integrated curriculum is viewed as the best solution to resolve this critical problem among contemporary Muslim scholars including Said Nursi. His view regarding the concept of integrated curriculum could be elucidated from his Madrasah Zahra model that promotes teaching of positive sciences in religious schools while religious subjects in the secular schools. This to make sure the products of religious education system are preserved from religious intolerance whereas the products of secular one from irreligious ethics. Integrated curriculum represents the epistemological aspect of Islamic education is a great challenge. Nonetheless, Nursi has positively proposed a holistic model of an Islamic University with an integrated knowledge based on Quranic framework and scientific advancements. Nursi’s concept of integrated curriculum based on his Madrasah al-Zahra model gives some implications in remodeling Islamic integrated curriculum for Muslim educational institutions in the effort of resolving Muslim problems and then, reviving Islamic civilization for the betterment of the whole mankind.